PENINGKATAN RENDEMEN DAN DAYA SERAP ARANG AKTIF DENGAN CARA KIMIA DOSIS RENDAH DAN GASIFIKASI (Improvement on recovery and quality of activated charcoal through low dossage chemical and gasification treatment) - Hartoyo Hartoyo; Gustan Pari (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
Study for improving the recovery and quality of activated charcoal through the combination of chemical and gasification treatments is presented in this paper. The material used in this experiments was charcoal derived from coconut shell. The material was immersed respectively in NaOH, Na2CO3, H3PO4 and ZnCl2 for 24 hours. Charcoal activation was conduted by using steam or combination of steam and mixed C02 and N2. The activated charcoal was produced in a stainless steel retort with electric heater at temperature of 900 - 1000°C.The result shows that the low dossage chemical treatment using NaOH at a concentration of 0,75%, or Na2C03 at a concentration of 0,75%, or ZnCl2 at a concentration of 5%, followed by activation by steam or the combination of steam and mixed C02 and N2.could produce good.quality activated charcoal which fullfils the commercial standard according to JIS. The produced charcoal attained the iodine adsorptive capacity of more than 1050 mg/g. By increasing the concentration of ZnCI2 to 10% or H3P04 to 20 %. followed by steam activation at 900°C - 1000°C, the iodine adsorptive capacity increased to more than 1200 mg/g.